Avanços da anestesia regional obstétrica - Krum, Francisco Fritsch Machry (2023)
The chapter "Advances in Regional Obstetric Anesthesia" covers the evolution of obstetric anesthesia, from the introduction of volatile anesthesia in the 19th century to modern techniques. The importance of neuraxial analgesia for parturients is emphasized, particularly spinal anesthesia in cesarean sections, due to its efficacy and psychological advantages. The use of ultrasound in neuraxial anesthesia is explored, highlighting its contribution to procedure accuracy and safety. Studies demonstrate that ultrasound assists in locating intervertebral spaces, reducing failures and complications. Fascial blocks,such as TAP and QL, are discussed as adjuncts to post-operative analgesia, with an emphasis on their effectiveness in pain reduction. The methodology employed in the chapter included exploratory research, a comprehensive literature review on online research portals, and the creation of a book chapter grounded in the collected information. The aim is to disseminate knowledge and drive advancements in obstetric regional anesthesia, revisiting the historical past and the latest techniques.